Optimizing Mathematical Representation Skills: Unveiling the Synergy between Quantum Teaching and Self-Esteem - Nanang Supriadi; Fredi Ganda Putra; Emita Cahyaningtyas; Khoirunnisa Imama (Engiscience Publisher, 2024)
The ability in mathematical representation, encompassing visual, verbal, and symbolic aspects serves as a critical foundation in mathematics education. This study examines the impact of the quantum learning model and self-esteem enhancement on the advancement of these abilities in students. The primary aim of this research is to optimize students' mathematical representation abilities through the implementation of the quantum learning model and self-esteem enhancement approaches. This quantitative study involved all eighth-grade students at a junior high school as the population, with a sample consisting of 34 students in class VIII B participating in the quantum learning model and 34 students in class VIII C following the discovery learning model. Samples were obtained through cluster random sampling techniques. A quasi-experimental design was utilized as the research method, with data collection through a self-esteem questionnaire containing 18 statement items and a mathematical representation ability test comprising 5 statistical material questions. Data analysis was conducted using one-way ANCOVA (analysis of covariance). The findings indicate that the quantum learning model combined with self-esteem enhancement significantly influences the improvement of students' mathematical representation abilities, compared to the discovery learning model. The application of the quantum learning model along with self-esteem enhancement strategies has proven effective in optimizing students' mathematical representation abilities. This underscores the importance of integrating innovative teaching methods and psychological approaches in mathematics education to facilitate deeper conceptual understanding and improve student learning achievements.